2010
DOI: 10.1007/s12664-010-0051-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of insulinoma: analysis from a tertiary care referral center in India

Abstract: This audit shows that all patients with insulinoma develop hypoglycemia within 48 h of fasting. CT of pancreas localizes the lesion in two thirds of cases and would be a useful initial investigation in patients with suspected insulinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…A review of the relevant studies published from India was also compared and contrasted with the current study and the findings are summarized in Table 4 . [ 25 29 30 31 32 ] We found a male preponderance in our series which was like a prior report from India, contrasting with many Western series with female preponderance. Further, while the calculated sensitivity of CT scan was similar to our study, MRI in this series demonstrated better sensitivity than our study (85.7% vs 64.3%).…”
Section: Discussionsupporting
confidence: 81%
“…A review of the relevant studies published from India was also compared and contrasted with the current study and the findings are summarized in Table 4 . [ 25 29 30 31 32 ] We found a male preponderance in our series which was like a prior report from India, contrasting with many Western series with female preponderance. Further, while the calculated sensitivity of CT scan was similar to our study, MRI in this series demonstrated better sensitivity than our study (85.7% vs 64.3%).…”
Section: Discussionsupporting
confidence: 81%